Mauritius : Staff Report for the 2017 Article IV Consultation-Press Release and Staff Report. (IMF Staff Country Reports; Country Report ;, 2017)
This 2017 Article IV Consultation highlights that the international reserve buffers have improved substantially in Mauritius. The government intends to pursue an ambitious growth strategy anchored on significant public investments in infrastructure and improvements in the business environment. Growth is projected at 3.9 percent in 2017, and about 4.0 percent over the medium term. The authorities have taken steps to mitigate financial stability risks and are well-advanced in modernizing financial sector regulation. However, the vibrant Global Business Sector faces pressure from international anti-tax avoidance initiatives. Fiscal space is limited, fiscal risks are increasing, and there are signs of building inflationary pressures.